FTO Prevents Thyroid Cancer Progression by SLC7A11 m6A Methylation in a Ferroptosis-Dependent Manner - Ji, Fei-Hong; Fu, Xing-Hao; Li, Guo-Quan; He, Qi; Qiu, Xin-Guang (Frontiers in Endocrinology, 2022)
N6 methyladenosine (m6A) modification serves as a novel epigenetic regulatory that is heavily implicated in heredity of tumors. Meanwhile, FTO has the potential to affect the regulation of m6A modification in the mRNA of key oncogenes as well as tumor suppressor genes those facilitate tumor progression. In our study, FTO was down-regulated in PTC tissues. The role of FTO in PTC was assessed by CCK-8 analysis, cell scratch, migration, invasion experiment, flow cytometry apoptosis analysis and nude mouse experiment. In addition to RNA-Seq and meRIP-Seq, luciferase reporting and mutation analysis have also identified SLC7A11 as the potential FTO regulatory gene. Moreover, X-ray electron microscopy, GSH / GSSG, GPX, MDA determination and Western blot helped confirmed that FTO inhibited the development of PTC by downregulating the expression of SLC7A11 through ferroptosis . Finally, a rescue experiment was employed to clarify the relationship between FTO and its specific target gene SLC7A11. FTO is able to inhibit the occurrence of PTC by downregulating SLC7A11 in m6A independently, and it functions as a tumor suppressor gene in PTC. These findings could contribute to our understanding of the tumor malignancy regulated by m6A and might lead to new insights for potential biomarkers and therapeutic targets for the treatment of thyroid papillary carcinoma.